Synthesis and Antibacterial Activities of New β-Lactam and Imidazole Derivatives - Hind J. Shawkat (Journal of Global Pharma Technology, 2018)
New β-lactam, imidazole, oxazole and amide derivatives were synthesized with good yields using simple methodology. Thiosemicarbazide derivatives 2(a-f) were treatment with ethyl chloro acetate to give compounds 1-((arylidene) amino) 2-thioxoimidazolidin-4-one 3(a-f), then3 (a-f) were converted to oxazole derivatives have β-lactam moiety by reaction with chloro acetyl chloride. Amide derivatives were synthesized by convertion 3(a-f) with acid chloride (acetyl chloride and benzoyl chloride).Structural of all derivatives have been confirmed with IR, H1 NMR and some of them with mass spectroscopy .These derivatives were tested for invetro antibacterial against Staphylococcus aureus, Pseudomonasaeruginosa Kelebsiella pneumonia and Escherichia Coli.Large number of compounds showed high inhibition zone (mm) against different bacterial species.Keywords: Imidazole, Oxazole,β-lactam, Amide, Antibacterial activity.